The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0002-9440(10)64431-8
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12 Alleviates the Skeletal Muscle Pathology in mdx Dystrophic Mice

Abstract: Muscular dystrophy is characterized by muscle degeneration and insufficient regeneration and replacement of muscle fibers by connective tissue. New therapeutic strategies directed toward various forms of muscular dystrophy are needed to preserve muscle mass and promote regeneration. In this study we examined the role of the transmembrane ADAM12, a disintegrin and metalloprotease, which is normally associated with development and regeneration of skeletal muscle. We demonstrate that ADAM12 overexpression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 43 publications
(55 reference statements)
0
48
0
1
Order By: Relevance
“…Since no alterations in transcription of the genes encoding the components of the dystrophin glycoprotein complex were observed in both array analyses, it is likely that the enhanced structural linkage and signaling provided by increased integrin accounts for the alleviation of dystrophic pathology in ␣ 7 -transgenic mdx/utrn Ϫ/Ϫ mice (12, 13). Array analysis of ADAM12 transgenic mice, in which an increase in ADAM12 partially rescued mdx mice, reported an increase of ␣ 7 -protein but not mRNA in skeletal muscle (41,51). In both our cell and tissue arrays, no significant change in transcription of any of the ADAM genes was detected, which suggests that ␣ 7 ␤ 1 -integrin may function downstream or in concert with ADAM12 in promoting muscle regeneration and preventing muscular dystrophy.…”
Section: Inducible Expression and Localization Of ␣ 7 -Integrin In C2mentioning
confidence: 51%
“…Since no alterations in transcription of the genes encoding the components of the dystrophin glycoprotein complex were observed in both array analyses, it is likely that the enhanced structural linkage and signaling provided by increased integrin accounts for the alleviation of dystrophic pathology in ␣ 7 -transgenic mdx/utrn Ϫ/Ϫ mice (12, 13). Array analysis of ADAM12 transgenic mice, in which an increase in ADAM12 partially rescued mdx mice, reported an increase of ␣ 7 -protein but not mRNA in skeletal muscle (41,51). In both our cell and tissue arrays, no significant change in transcription of any of the ADAM genes was detected, which suggests that ␣ 7 ␤ 1 -integrin may function downstream or in concert with ADAM12 in promoting muscle regeneration and preventing muscular dystrophy.…”
Section: Inducible Expression and Localization Of ␣ 7 -Integrin In C2mentioning
confidence: 51%
“…The secreted form ADAM12-S can cleave insulin-like growth factor (IGF)-binding protein-3 and -5 Shi et al, 2000), and in so doing promotes bioactivity of IGF-1 and -2, two positive regulators of muscle growth, survival, and regeneration (Husmann et al, 1996;Kaliman et al, 1996;Kronqvist et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, constitutive muscle expression of ADAM12 starts at the embryonic stage when myotubes are formed (Kurisaki et al, 1998), persists at the neonatal stage (Yagami-Hiromasa et al, 1995;Borneman et al, 2000;Kronqvist et al, 2002), and ceases in adulthood (Borneman et al, 2000;Kronqvist et al, 2002). Adult muscle regeneration after experimental injury is associated with ADAM12 reexpression by fusing myogenic cells and newly formed fibers (Galliano et al, 2000;Kronqvist et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…ADAM12, originally named meltrin-␣ (25), has been implicated in muscle cell function in vivo and in vitro (25)(26)(27)(28)(29)(30). In the original study, expression of a truncated version of ADAM12, lacking the prodomain and metalloprotease domain, was found to stimulate muscle-cell fusion in cultured C2C12 cells, whereas full-length ADAM12 inhibited the fusion process (25).…”
mentioning
confidence: 99%
“…The level of cell-surface ADAM12 seemed to be highest at the onset of differentiation. These and other studies have demonstrated that ADAM12 has a specific temporal expression pattern in several tissue compartments during development, regeneration, and in disease (12,18,19,(23)(24)(25)(26)(27)(28)(29)(30)33). However, little is known about the regulation of ADAM12 activation and translocation to the cell surface.…”
mentioning
confidence: 99%